Analisis Penegakan Hukum Tindak Pidana Korupsi pada Era Digital Serta Bagaimana untuk Membantu Mengungkapkan dan Menghentikan Korupsi - Abdullah Husein Al Aziz; Zainudin Hasan; Irfan Raihan Hady Fauzi; Mansah Mansah (Pusat Riset dan Inovasi Nasional, 2025)
In the digital era, anti-corruption law enforcement faces new challenges and opportunities. With the development of information technology, corrupt practices are increasingly complex and hidden, committing fraud and embezzlement by utilizing digital space. The use of advanced technologies such as big data analysis, artificial intelligence, and blockchain are some examples of how law enforcement can tackle corruption. In addition, this study investigates various ways in which the government, law enforcement agencies, and civil society can work together to improve transparency and accountability. It is expected to improve anti-corruption efforts by utilizing digital platforms to report and detect suspicious activities. The study found that adapting law enforcement to technological changes is important to uncover and stop corrupt practices in the digital era. In addition, public education is essential to building a stronger anti-corruption culture. To create a transparent government, the role of the media and public participation is very important to increase the accountability of officials for corrupt practices. This study aims to see how public participation and the media monitor corruption and to find methods that can improve such supervision. The methods used include literature research, reports, and policy articles. The results of the study indicate that taking an active part in reporting and monitoring can increase the accountability of public officials.